Fischer-Tropsch Synthesis on Co/SiO2 Catalysts with Potassium Promoter - Atashi, Hossein; Sahebi-shahemabadi, Mehdi; Akhavan, Reza (Asian Journal of Chemistry, 2010)
The effects of potassium-promoted Co/SiO2 Fischer-Tropsch synthesis catalysts were investigated. After preparing the catalysts in accordance with the sol-gel method, they were subjected to various tests by using a small steely micro-reactor and finally, catalyst testing was performed under specific conditions [t = 220 °C, P = 7 atm, H2/CO = 2, 6E-4 GHSV]. Catalysts were characterized by X-ray diffraction. The addition of potassium oxychloride (0-10 wt % of K) to silica-supported cobalt catalysts has been studied and some of the results are as follows: decrease in BET surface area of the resulted catalysts and in methane selectivity, increase in CO conversion, reaction rate, C5+, C10+ and C22+ selectivity, decrease in the formation of activation energy of the heavy hydrocarbons in comparison with methane and change of product distribution towards the heavier hydrocarbons. Reactions such as cracking, isomerizing and hydrocracking can also be minimized on base construction of catalyst.